Knowledge of the specific contente mobilized by Pedagogy students on symmetry - Luciana Ferreira dos Santos; Rosinalda Aurora de Melo Teles (Pesquisa e Ensino, 2020)
In this article, taking into account the categories of teaching knowledge by Shulman (1986), knowledge of the specific content of Pedagogy students about symmetry is analyzed. Research of qualitative and quantitative nature, used as a tool for data collection three problem situations involving identifying symmetrical figures; identify the axis of symmetry and complete symmetrical figures. The low success rates, in all questions, indicate that the knowledge of the investigated students is still insufficient to work on the content, even in situations proposed in mathematics textbooks of the early years. The data also point to indications of knowledge about reflection symmetry and different positions of the axis, but still insufficient to solve problem situations. The results obtained can support teaching actions that positively impact the pedagogical training of Pedagogues, as the mastery of specific content in several areas of education is essential for the training and performance of these professionals.